Hippolytus - Euripides (punctum books, 2012)
Euripides wrote two plays called Hippolytus. In this, the second, he dramatized the tragic failure of perfection. This translation comes in two forms; the first presents a simulacrum of the text as it might have appeared in unprocessed form to a reader sometime shortly after Euripides' death. The second processes the drama into the reduced but much more distinct form of modern print translations.